2018
DOI: 10.2337/db18-1286-p
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Machine Learning Algorithm Improves Prediction of Progression to Diabetes

Abstract: Identification a-priori of subjects at high risk of progression from prediabetes to diabetes may enable targeted delivery of interventional programs, while avoiding the burden of prevention and treatment in those at low risk. This study relies on the NHS THIN database cohort of 2,761,222 persons with at least 2 glucose measurements during an average follow-up of 6 years. Prediabetes was diagnosed in 470,107 persons, with 4.8% of them progressing annually to diabetes. We constructed a non-linear model identifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For instance, a study comparing different machine learning techniques found that decision trees outperformed others in terms of accuracy 25 . Additionally, Cahn et al 26 demonstrated the prediction of diabetes risk using logistic regression and achieved commendable specificity rates. Various machine learning methods have also been explored for hypertension risk prediction.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study comparing different machine learning techniques found that decision trees outperformed others in terms of accuracy 25 . Additionally, Cahn et al 26 demonstrated the prediction of diabetes risk using logistic regression and achieved commendable specificity rates. Various machine learning methods have also been explored for hypertension risk prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review indicates that mobile apps and related technology can positively affect health aspects, in particular weight loss, as well as diabetes prevention and treatment [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Similarly, an initial literature review indicates a significant number of publications on the use of Artificial Intelligence and Machine Learning techniques for diabetes prediction, prevention, and treatment [ 28 , 29 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Methodology and Contextual Approachmentioning
confidence: 99%
“…and Cahn et al [28] built risk models aiming for diabetes. Seyednasrollah et al and Chen et al achieved a high predictive power in obesity risk prediction [29] [30].…”
Section: Introductionmentioning
confidence: 99%
“…For example, there are risk estimation models for hypertension patients [22] , [23] , [24] , [25] . Also, Luo et al [26] , Casanova et al [27] , and Cahn et al [28] built risk models aiming for diabetes. Seyednasrollah et al and Chen et al achieved a high predictive power in obesity risk prediction [29] [30] .…”
Section: Introductionmentioning
confidence: 99%